Passive Radar Signatures of Micro-Drone and Birds - Vorobev, Evgenii; Veremyev, Vladimir; Kutuzov, Vladimir (Proceedings of the IEEE Radar Conference, 2019)
This paper presents the results of experimental investigations of the micro-Doppler signatures of the micro-drone and birds observed in passive radar exploiting DVB-T2 illuminators of opportunity. The contribution from flapping wings on the structure of the bird's Doppler signature is studied. The distinct features promising for discrimination between the detections of drone or birds are revealed.